The family participation of grandparents/grandmothers in old age. Special reflections on the right to feed (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
In this work we address the right to feed grandparents and grandmothers to grandchildren as part of the rights of participation or family inclusion recognized in favor of the elderly. This group of rights integrates the object of Old Age Law, an autonomous legal branch that deals with the problems caused by aging through legal responses that arise from formal sources and specific assessments. The food duty-right of grandparents and grandmothers gives rise to one of the most important intra-family and intergenerational interactions in Family Law. We believe it is appropriate to use the expression "alimentary relationship" to consider not only the normative aspects but also social and evaluative ones, and with this shed light on the importance of considering from the legal world the contexts, values, socio-cultural constructions on old age, belonging, interaction, grandparentage, among others.
Keywords: Relation food-stake; grandparents; grandmothers; old age; legal area